Using Conversion as a Way of Forming Words in English and Karakalpak Languages - Badirova Dilfuza Asamatdinovna (Zien Journals, 2022)
The article introduces the study of conversion process in English and Karakalpak languages. The investigation considers some widely-spread transition of Word-formation in modern English and Karakalpak languages by means of conversional patterns. The ways of their secondary nomination are also being discussed, as well as acquiring additional meanings while functioning in speech. It is well known that the phenomenon of conversion is so active in modern English that nearly all parts of speech somehow are involved into this process, however in different extent – most oftener they are nouns, verbs, adjectives and adverbs.
Keywords: Word formation; conversion; investigate; process